When is tit-for-tat unbeatable? - Peter Duersch; Joerg Oechssler; Burkhard C. Schipper (University of California, Department of Economics, 2013)
We characterize the class of symmetric two-player games in which tit-for-tat cannot be beaten even by very sophisticated opponents in a repeated game. It turns out to be the class of exact potential games. More generally, there is a class of simple imitation rules that includes tit-for-tat but also imitate-the-best and imitate-if-better. Every decision rule in this class is essentially unbeatable in exact potential games. Our results apply to many interesting games including all symmetric 2x2 games, and standard examples of Cournot duopoly, price competition, public goods games, common pool resource games, and minimum effort coordination games.
Keywords: C72; C73; D43; 330; imitation; tit-for-tat; decision rules; learning; exact potential games; symmetric games; repeated games; relative payoffs; zero-sum games